Respuesta :

Answer:

[tex]f(x) = 3 {x}^{2} \\ lim \: \frac{f(x + h) - f(x)}{h} \: \: when \: h - > 0 \\ lim \: \frac{3( x + h)^{2} - 3 {x}^{2} }{h} when \: h - > 0 \\ lim \: \frac{3( {x}^{2} + 2xh + {h}^{2}) - 3 {x}^{2} }{h} when \: h - > 0 \\ \\ lim \: \frac{3 {x}^{2} + 6xh + 3h^{2} - 3 {x}^{2} }{h} when \: h - > 0 \\ lim \: \frac{6xh + 3 {h}^{2} }{h} \: when \: h - > 0 \\lim \frac{6xh}{h} + \frac{3h^{2} }{h}when \: h - > 0 \\ lim \: 6x + 3h \: when \: h - > 0 \\ = 6x + 3(0) \\ = 6x + 0 \\ = 6x \\ \\ or \\ \frac{d(3x^{2}) }{dx} = 2 \times 3x^{2 - 1} \\ = 2 \times 3x^{1} \\ = 2 \times 3x \\ = 6x[/tex]